The genus Armandia Filippi, 1861 (Annelida, Opheliidae) on the coast of Kuwait and Saudi Arabia - Parapar, Julio; Al-Kandari, Manal; Moreira, Juan (Zootaxa, 2025)
Samples collected in intertidal and shallow subtidal localities along the coast of Kuwait and Saudi Arabia yielded five species of the genus Armandia Filippi, 1861 (Annelida, Opheliidae) that are newly reported in the Arabian Gulf: Armandia bipapillata Hartmann-Schröder, 1974, Armandia aff. dolio Parapar & Moreira, 2015, Armandia melanura Gravier, 1905, Armandia sinaitica Amoureux, 1983 and Armandia aff. weissenbornii Kükenthal, 1887. All species are fully described, illustrated, and compared with similar species and those previously reported in the area. A key for species of Armandia in the Indo-Pacific, Southern Asia, Indo-Malay Archipelago and Australia, is also provided.